Evaluation of the anti-candidal activity of the ointment formulation containing the admixture of Allium sativum (Liliaceae) and Citrus sinensis (Rutaceae) - Salako, Kehinde S.; Silva, Boladale O.; Azubuike, Chukwuemeka P.; Salako, Olanrewaju A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2018)
Candidiasis is a highly recurring disease with an history of resistance, thus the need for discovering newer anti-fungal drugs. The aim of this study was to evaluate the anti-candidal activity of the admixture of Allium sativum bulb (ASB) and Citrus sinensis peel (CSP) extracts and its ointment formulation. The in vitro anti-candidal activity of the admixtures and the formulated admixture was evaluated using agar well diffusion method and the minimum inhibitory concentration (MIC) was obtained using solid dilution method. The anti-candidal activity of the admixtures in the ratios 1:1, 1:2 and 2:1 at the concentration of 50 mg/mL gave zones of inhibitions (mm) of 15.50, 21.00 and 16.50 respectively. The zone of inhibition (18.50 mm) of ASB extract at this concentration was smaller than that of the admixture (1:2) while that of the formulated admixture (25.50 mm) was higher than the admixture (1:2). The formulated admixture gave no sensation and was poorly homogenous in appearance. It had a pH of 6.89. Also, the nauseating odour of ASB extract was reduced in the formulation containing the admixture.